History of the Appearance of Infinite-Dimensional Analysis and its Development in Ukraine - Gorbachuk, M. L. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We present a brief survey of the development of functional analysis in Ukraine and the problems of infinite-dimensional analysis posed and solved for thousands of years, which laid the foundations of this branch of mathematics.